Mapping key concepts of e-learning and educational-systematic review through published papers - Rodrigues, H.; Almeida, F.; Figueiredo, V.; Lopes, S. (11th annual International Conference of Education, Research and Innovation, 2018)
E-Learning also known as electronic learning has gained a wide acceptance from all educational fields and academic institutions. In the past decades we have experienced a profound growth of e-learning courses in education and multiple systems have appeared from medicine to management covering different needs and users. Previous studies indicate a proliferation and discrepancy of e-learning contents that affect interoperability patterns in education for students, teachers and academic staff and have done little to assess the usability of e-learning educational systems leading to contradictory findings that can mislead academics and users.